TREND IN THE PLACEMENT OF PERMANENT AND TEMPORARY CENTRAL VENOUS CATHETERS FOR HEMODIALYSIS - Peličić, Damir; Mucic, Elvir (Sanamed, 2026)
Dear Editor Chronic kidney disease (CKD) is one of the fastest-growing diseases worldwide (1). As the world population ages, the incidence of renal failure is increasing globally, along with the prevalence of people receiving chronic dialysis. There are three renal replacement modalities: peritoneal dialysis (PD), transplantation (Tx), and hemodialysis (HD), HD being the most common form of dialysis, with a worldwide prevalence of 89%, with PD accounting for the remaining 11%. The standard approach for HD is the arteriovenous fistula (AVF), while an alternative vascular access device for HD, still the tunneled central venous catheter (CVC) (1,2), is a salvage vascular access option for HD, but it is still used in approximately one-quarter of prevalent patients worldwide, although it is associated with poor performance and higher risks (2). The literature suggests that CVC remains the most commonly used vascular access option for HD, despite guidelines advising that AVFs should be used whenever possible. The risk of CVC has mostly focused on catheter-related bacteremia and/or has only evaluated tunneled CVCs (TCVKs) (3). CVCs were first used in a patient in 1969. Over time, indications for their use have become more numerous, such as parenteral nutrition, chemotherapy, and situations where peripheral venous access is not possible in patients in intensive care units. CVC placement involves the placement of a catheter in a large-lumen venous system, most commonly the internal jugular, subclavian, or femoral vein. Complications associated with CVC placement occur in 2–26% of cases, so its use is rare and is most often in acute renal failure (4). Globally, almost three-quarters of patients on HD require a CVC (5,6). CVCs provide immediate access to hemodialysis in cases where high nitrogenous wastes, hyperkalemia, and anuria require urgent HD, but the use of a catheter is thought to increase the risk of complications associated with placement and long-term use (7). In patients on HD, CVCs are used when other vascular access options are not available (8–11). Since the introduction of CVCs, catheters have been coated with heparin or antibiotics, and catheter-related complications are less common (12,13). The literature suggests that CVC-associated bloodstream infections in patients on HD are an important cause of hospitalization, morbidity, and mortality. Eliminating bloodstream infections in the hemodialysis setting has been a focus of the Centers for Disease Control and Prevention (CDC) Coalition (14,15,16). General preventive measures, including the use of asepsis and antisepsis, play a key role in the prevention and early detection of CVC-associated infections in patients on HD. Infection control surveillance, together with a team approach to care (doctor–nurse), significantly contributes to the reduction of CVC-related morbidity and mortality (4). Our data from the Nephrology Clinic show that in 2025, out of approximately eighty patients on HD, 14 had a temporary or permanent CVC. Our HD center does not differ significantly from other centers in terms of the trend of CVC placement and the occurrence of complications, which can be explained by the correct placement and monitoring of therapeutic guidelines by anesthesiologists and nephrologists, and the correct maintenance and hygiene of CVCs by educated nurses in the dialysis center, Nephrology Clinic, Clinical Center of Montenegro, and the application of asepsis and antisepsis measures. Continuous evaluation, proper care and hygiene of dialysis catheters, and early detection of patients with end-stage renal disease are recommended in order to initiate HD on time and thereby prevent complications and reduce morbidity and mortality rates, with the aim of extending life expectancy and improving the quality of life of patients on HD.